Both Castration and Goserelin Acetate Ameliorate Myocardial Ischemia Reperfusion Injury and Apoptosis in Male Rats. (3rd March 2014) - Hadi, Najah R.; Yusif, Fadhil G.; Yousif, Maitham; Jaen, Karrar K.
Abstract : Although reperfusion of an ischemic organ is essential to prevent irreversible tissue damage, it may amplify tissue injury. This study investigates the role of endogenous testosterone in myocardial ischemia reperfusion and apoptosis in male rats. Material and method . Twenty four male rats were randomized into 4 equal groups: Group (1), sham group, rats underwent the same anesthetic and surgical procedure as the control group except for LAD ligation; Group (2), Active control group, rats underwent LAD ligation; Group (3), castrated, rats underwent surgical castration, left 3wks for recovery, and then underwent LAD ligation; and Group (4), Goserelin acetate treated, rats received 3.6 mg of Goserelin 3 wks before surgery and then underwent LAD ligation. At the end of experiment, plasma cTn I, cardiac TNF- α, IL1- β, ICAM-1, and Apoptosis level were measured and histological examination was made. Results . Compared to sham group, the levels of myocardial TNF- α, IL-1 β, ICAM-1, apoptosis, and plasma cTn I were significantly increased (P < 0.05 ) in control group and all rats showed significant myocardial injury (P < 0.05 ). Castration and Goserelin acetates significantly counteract the increase in myocardial levels of TNF- α, IL-1 β, ICAM-1, plasma cTn I, and apoptosis (P < 0.05 ) and significantly reduce (P < 0.05 ) the severity of myocardial injury. We conclude that castration and Goserelin acetates ameliorate myocardial I/R injury and apoptosis in rats via interfering with inflammatory reactions.